Digitalisasi Ekonomi Syariah dalam 12 Aspek Isomorfisme: Kontekstual Indonesia - Rachmad Nor Firman (Universitas Islam Raden Rahmat, 2023)
The digitalization of the Islamic economy can penetrate various aspects of the economy, both microeconomics and macroeconomics. Right now, the role of digital is extraordinary; almost all economies use information and communication technology or digitization, both in packaging products and in marketing products, making it easier and faster the distribution information used to make economic growth faster and without limits with the support digital technology and information technology. Information technology that has penetrated individuals (personal) can support the era of digitalization of information and communication in conventional economics and Islamic economics; this technology is now in the hands of gadget users, such as mobile applications, which can be downloaded and installed with features easily understood by users. Likewise, in the banking world, in carrying out its activities, Islamic banking cooperates with the information technology sector to build an Islamic banking information system by creating a special application (app) that can facilitate all transaction processes in banking. So, the formation of a digital society, one of which is the digital Islamic economy.